Konstruksi Economic Analysis of Law dalam Penerapan Konsep Ekonomi Hijau di Sektor Energi Baru dan Terbarukan - Krismawan, Deny Andreas; Syaputri, Martika Dini; Butarbutar, Elisabeth N. (Universitas Negeri Malang, 2025)
This study aims to analyze the arrangement of the green economy concept in the regulation of new renewable energy, the construction of the application of economic analysis of law in the regulation of the green economy in the regulation of new renewable energy, as well as the principle of green constitution in the transition to new renewable energy. This study used a normative juridical research method with a legislative approach and a conceptual approach. The results of the study indicate that the regulation of new renewable energy requires a special law that regulates comprehensively based on the principles of a green economy. The construction of new renewable energy law through the application of the concept of economic analysis of law is expected to be able to contain values, efficiency, and used that can provide benefits for the economy and environmental sustainability. Article 33 paragraph (4) of the 1945 Constitution of the Republic of Indonesia affirms the principle of just and environmentally friendly economic democracy as the basis of a green constitution for the application of new renewable energy